Indocyanine green (ICG) fluorescence‐guided laparoscopic adrenalectomy. Issue 6 (29th September 2015) - DeLong, Jonathan C.; Chakedis, Jeffrey M.; Hosseini, Ava; Kelly, Kaitlyn J.; Horgan, Santiago; Bouvet, Michael
<x xml:space="preserve">Abstract</x> Objective Laparoscopic adrenalectomy has become the standard of care for many adrenal tumors. However, the success of the operation hinges on identifying the adrenal vein and complete tumor resection. We demonstrate the use of a commercially available near infrared fluorescent imaging system to clearly delineate the vascular anatomy of adrenal neoplasms and enhance the border between tumor and normal tissue. We hypothesize that this will increase the safety of laparoscopic adrenalectomy. Materials and Methods We performed laparoscopic adrenalectomy utilizing indocyanine green (ICG) and a specialized laparoscopic fluorescence imaging system on four consecutive patients undergoing laparoscopic adrenalectomy over a 4‐month period. Results The adrenal arteries and vein were vividly enhanced with ICG fluorescence guidance, and the border between tumor and adjacent tissue was clearly demarcated. The operations were performed safely with minimal blood loss and short operative times. There were no complications. Conclusions Adrenal neoplasms can be resected laparoscopically under ICG fluorescence guidance and can be used to clearly identify vascular structures and enhance the borders of the tumor. This technique allows for clear identification of the adrenal vein and has the potential to improve the safety of laparoscopic adrenalectomy. J. Surg. Oncol. 2015;112:650–653. © 2015 Wiley Periodicals, Inc.